Preemptive Circular Defence of Immature Insects: Definition and Occurrences of Cycloalexy Revisited. (24th March 2014) - Dury, Guillaume J.; Bede, Jacqueline C.; Windsor, Donald M.
Abstract : Cycloalexy was coined by Vasconcellos-Neto and Jolivet in 1988 and further defined by Jolivet and collaborators in 1990 in reference to a specific type of circular defence. The term has been applied to numerous organisms, including adult insects, nymphs, and even vertebrates, but has lost precision with the accumulation of anecdotal reports not addressing key elements of the behaviour as first defined. We review the literature and propose three criteria that are sufficient and necessary to define the behaviour: (1) individuals form a circle; (2) defensive attributes of the individuals are positioned on the periphery of the circle, and as a result, the periphery of the circle uniformly contains either heads or abdomens; (3) animals preemptively adopt the circle as a resting formation, meaning it is not necessary to observe predation. When these considerations are taken into account, cycloalexy appears less common in nature than the literature suggests. We argue that unequivocal cases of cycloalexy have been found only in sawflies (Tenthredinoidea: Pergidae, Argidae), leaf beetles (Chrysolemidae: Galerucinae, Cassidinae, Chrysomelinae, Criocerinae), weevils (Curculionidae: Phelypera distigma ), and midges (Diptera: Ceratopogonidae, Forcipomyia ). Reports of cycloalexy in caterpillars (Saturniidae: Hemileucinae: Lonomia, Papilionidae) require further documentation. We report one new case of cycloalexy in thrips (Thysanoptera) and question reports of cycloalexic behaviour in other taxa.